Hadrontherapy techniques for breast cancer. (January 2022) - Loap, Pierre; De Marzi, Ludovic; Almeida, Carlos Eduardo; Barcellini, Amelia; Bradley, Julie; de Santis, Maria Carmen; Dendale, Remi; Jimenez, Rachel; Orlandi, Ester; Kirova, Youlia
Graphical abstract: Highlights: Breast hadrontherapy techniques include proton therapy, carbon ion radiotherapy, fast neutron therapy and boron neutron capture therapy. Proton therapy is expected to reduce late cardiotoxicity but optimal patient selection is subject to debate. Carbon ion radiotherapy has radiobiological advantages, is effective and well-tolerated for unresectable tumors and might be used for radioresistant histologies. Fast neutron therapy is effective for unresectable chemo-refractory primary tumors or chest wall recurrences, but its availability is limited. Boron neutron capture therapy is under development for unresectable locoregional recurrences and metastatic tumors. Abstract: Radiotherapy plays a key role in breast cancer treatment, and recent technical advances have been made to improve the therapeutic window by limiting the risk of radiation-induced toxicity or by increasing tumor control. Hadrontherapy is a form a radiotherapy relying on particle beams; compared with photon beams, particle beams have specific physical, radiobiological and immunological properties, which can be valuable in diverse clinical situations. To date, available hadrontherapy techniques for breast cancer irradiation include proton therapy, carbon ion radiation therapy, fast neutron therapy and boron neutron capture therapy. This review analyzes the current rationale and level of evidence for each hadrontherapy technique for breast cancer.